Evaluación del desempeño de diferentes biomasas residuales sólidas como posible sustituto de nutrientes para cultivos de la microalga Chlorella Vulgaris (2024)
In this research, the growth of the microalga Chlorella vulgaris was compared with three different types of solid residual biomass: sugarcane bagasse, corn leaf and coffee husk, as a source of nutrients for better development of the microalga. Initially, the cultivation conditions were established according to a bibliographic review to initiate the growth of the microalga for three months. During this three-month period, theoretical analyses of the biomass were carried out, comparing the results provided of the chemical and physical composition of the biomass to be used, with the theoretical information of various investigations, where it was determined that sugarcane has a higher percentage of compounds that contribute positively to the microalga. Nutrients were extracted from each biomass and added to a new culture medium, where the microalgae was inoculated and growth began. The cultures were allowed to grow for a month and through periodic checks and according to the cell count, it was found that the corn leaf had a higher cell concentration value: 〖8.026x10〗^6 [cell/mL] compared to coffee 〖7.122x10〗^6 [cell/mL], sugarcane bagasse 〖5.856x10〗^6 [cell/mL] and the control 〖5.626 x10〗^6 [cell/mL]. Liquid chromatography-mass spectrometry analyses were performed, identifying 13 lipids in total in the samples, including 3 fatty acids, with sugarcane bagasse being the biomass with the highest amount. In the cost/benefit ratio, the costs of the composition of the culture media were evaluated together with the solvent used for the extraction of the nutrients and are related in a comparison analysis of the benefits of each biomass where it was determined that the corn leaf may be the most optimal for the microalgae.